Dynamic Seek and Release Model for Self-Learning Based Assessment - Shindhe, K. C.; Kulkarni, U. P. (Journal of Engineering Education Transformations, 2017)
Engineering education has become amain attraction, contributing to the global industry revolution and in particular to Indian economy. The exponential growth in technical education has, however, not translated into any significant growth in the number of quality graduates acceptable to industry, due to insufficient availability of qualified faculty, teaching methodology, evaluation techniques and processes. Increasing autonomous institutions and an introduction of a buzz word ’Self learning (SL)’, in its infancy stage in autonomous institution under Vishveshwaraya Technological University (VTU) and its impact on quality is amajormatter of concern. Author of this paper propose an induction of ’self - learning’ approach for autonomous Institutions,which allows everyone who wish to practice self-learning subjecting them to controlled scrutiny by Department Under Graduate Cell ( DUGC), an academic body at the department level responsible for all academic affairs of an autonomous Institution. It also ensures to keep off those faculties from practicing ’self-learning’, who have not fully understood this mechanism.